Alcoholic fermentation of lactose by engineered flocculent Saccharomyces cerevisiae - Guimarães, Pedro M. R. (2008)
The construction of Saccharomyces cerevisiae strains with the ability to ferment lactose has biotechnological interest, particularly for cheese whey fermentation to ethanol. Direct fermentation of whey to ethanol is generally not economically feasible because the low lactose content (ca. 5% w/v) results in low ethanol titre (2 – 3% v/v), making the distillation process too expensive. Concentration of whey lactose (e.g. by ultrafiltration) prior to fermentation is an option to obtain higher ethanol titres. Microbial strains are therefore needed that can efficiently convert high concentrations of lactose into ethanol. We describe here the engineering of a S. cerevisiae strain for efficient lactose fermentation, involving genetic and evolutionary engineering strategies. The evolved strain obtained fermented efficiently lactose concentrations up to 150 g L-1, including 3-fold concentrated cheese whey, producing ethanol titres up to 8% v/v. The strain is highly flocculent, a property that makes it particularly suitable for the development of high cell density fermentation processes.